Current state and principal tasks of hydrobotany in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
An analysis of development of hydrobotanical researches in Ukraine for the last 20 years has been presented. There have been distinguished and briefly described the scientific trends, such as floristic, systematic, morphology-biological, ecological, geobotanical, phytosozological and resources. The urgent issues of the further researches have been considered.
Keywords: hydrobotany, водні макрофіти, hydrophytes, water vegetations, hydrophytology.